Report on a portion of Conrad and Whitehorse mining districts, Yukon. - Geological Survey of Canada.; Cairnes, D. D. (DeLorme Donaldson), 1879-1917. (Ottawa, Printed for S.E. Dawson, 1908)
At head of title: Canada, Department of mines, Geological survey branch . Mode of access: Internet.